Analytical solution for predicting the interaction stress of axially loaded concrete-filled double-tube columns. (October 2022) - Li, Weijie; Liang, Hongjun; Li, Shan; Lu, Yiyan; Huang, Yue
Abstract: Concrete-filled double-tube (CFDT) members are promising steel-concrete composite structural forms. Existing studies mainly focus on members' load-deformation performance. The interaction stress between components, which is a fundamental cause for change in load-deformation performance, receives much less attention. This study presents an analytical solution for interaction stress between components of axially loaded CFDT columns. The stress–strain relationships and force equilibrium equations of the inner concrete, inner steel tube, sandwiched concrete, and outer steel tube were analysed using elasticity method first. Subsequently, the deformation compatibility equations were established concerning the interactions between the components. Based on the above analysis, an analytical solution was derived. Equivalent lateral deformation coefficients were used to substitute Poisson's ratio of concrete to account for the nonlinear behaviour of materials during loading. The proposed model shows reasonable agreement with experimental results. Finite element analysis further shows the accuracy of the interaction stress model till an axial compressive strain of 0.01 of the composite column. The derived interaction stress model was successfully applied in predicting the load-bearing capacities of CFDT columns through validation of 39 specimens from five independent studies. The average ratio of the predicted-to-experimental bearing capacities was 1.054, with a coefficient of variation of 0.077. The accuracy of models in Eurocode 4, ACI 318-11, and GB 50936 were also evaluated. Thereby the proposed model provides insights into the interaction analysis between components and mechanism-based load-bearing capacity prediction of CFDT columns. Highlights: Analytical solution for interaction stress between components of CFDT columns was proposed. Stress–strain relationships, force equilibrium equations, and compatibility equations were established for components. The interaction stress was successfully applied in predicting the load-bearing capacity of CFDT columns.